REMOÇÃO DE DQO, NITROGÊNIO E FÓSFORO DE ESGOTO SANITÁRIO EM REATOR DE LEITO ESTRUTURADO COM AERAÇÃO INTERMITENTE EM FASE ÚNICA - JENZURA, NATHANNA TESSARI (2017)
The phenomenon of eutrophication is characterized by excessive growth of algae due to excess nitrogen and phosphorus in water bodies. Combined with this factor, we have the fact that the Brazilian Effluent Treatment Plants (ETP) were designed to remove COD (Chemical Oxygen Demand) and not nutrients, so it is necessary the tertiary treatment to comply with the legislation. Research shows that there is the possibility of removing COD and nitrogen in a single compartment, which would generate savings in the implementation and operation of ETP. The objective of this research was to evaluate the efficiency of a structured bed reactor with intermittent and continuous flow in the removal of nitrogen and COD from the raw sanitary sewage mixed with UASB (Upflow Anaerobic Sludge Blanket) effluent. The reactor had a useful volume of 8,6 L. The structured bed was composed of 13 cylinders of polyurethane foam with a diameter of 2,5 cm and a length of 63 cm, arranged vertically inside the reactor. The feed was continuously fed with 50% crude sanitary sewage and 50% RALF effluent. The experiment was done following a factorial design 22, which resulted in seven tests with four points at the extreme levels (+1 and -1) and the triplicate of the central point. The factors and respective stipulated levels were HRT (Hydraulic Retention Times) of 8, 10 and 12 hours, and aeration time of 60, 75 and 90 minutes in 180 minute cycles. The recirculation ratio was equal to 2 times the inlet flow rate. Under these conditions were found to be COD removal average of 76% and NT (Total Nitrogen) of 83%. The best COD (92%) and NT (88%) efficiency results were found when the reactor operated with 60 minute aeration time and 8 hour HRT, having a final COD concentration of 18 mg.L-1 and NT of 4.3 mg.L-1. The response surface was used to verify the effects of the factors on the responses and to design a mathematic model to predict NT removal and nitrification. The results obtained allow us to consider that the structured bed reactor with intermittent aeration is a viable alternative for the simultaneous removal of COD and nitrogen compounds.The mathematical model obtained was predictive, and with a HRT of 9 hours and aeration of 60 minutes, the experimental responses for TN removal and nitrification efficiency was 81% and 89%, respectively, very close to the predicted one, that was 85% and 94%.